2006
DOI: 10.1148/radiol.2381050489
|View full text |Cite
|
Sign up to set email alerts
|

Small-Bowel Obstruction: Coronal Reformations from Isotropic Voxels at 16-Section Multi–Detector Row CT

Abstract: Transverse 16-section multi-detector row CT data sets are an excellent test for the diagnosis of SBO, while the addition of coronal reformations obtained from these isotropic data sets adds confidence to the diagnosis and exclusion of SBO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 33 publications
3
18
0
1
Order By: Relevance
“…However, only two studies (published by the same team) evaluated the added value of reformatting in acute abdomen cases, i.e. appendicitis and bowel obstruction [16,17]-so far no one has evaluated the role of thin slices and reformation in the diagnosis of bowel perforation, although Milki et al [18] reported one case of bowel perforation in which a comparison of 2-mmthick and 7-mm-thick axial slices was made. Our study was designed to determine the incremental diagnostic value of adding 1.25-mm slices and coronal and sagittal reformatting to 5-mm axial slices for identification of discontinuities in the GI wall, as a direct bowel perforation finding in patients with a pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…However, only two studies (published by the same team) evaluated the added value of reformatting in acute abdomen cases, i.e. appendicitis and bowel obstruction [16,17]-so far no one has evaluated the role of thin slices and reformation in the diagnosis of bowel perforation, although Milki et al [18] reported one case of bowel perforation in which a comparison of 2-mmthick and 7-mm-thick axial slices was made. Our study was designed to determine the incremental diagnostic value of adding 1.25-mm slices and coronal and sagittal reformatting to 5-mm axial slices for identification of discontinuities in the GI wall, as a direct bowel perforation finding in patients with a pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…Recent MDCT data using multiplanar reformations have not demonstrated significantly improved sensitivity and specificity for diagnosing SBO or its complications relative to evaluation of transverse images alone [7]. The use of coronal reformations has, however, been shown to increase confidence of the radiologist in the following areas: excluding SBO, diagnosing SBO, and demonstrating abnormal bowel wall enhancement [7].…”
Section: Sensitivity Of Ct In Small Bowel Obstruction and Related Finmentioning
confidence: 99%
“…The use of coronal reformations has, however, been shown to increase confidence of the radiologist in the following areas: excluding SBO, diagnosing SBO, and demonstrating abnormal bowel wall enhancement [7]. In addition, clinicians generally are appreciative of the more familiar anatomy demonstrated with multiplanar reformation and 3D sequences.…”
Section: Sensitivity Of Ct In Small Bowel Obstruction and Related Finmentioning
confidence: 99%
“…26,27 Isotropic voxel has advantages in the quality of the reconstruction of geometric model. [28][29][30][31][32] For instance, the use of submillimeter isotropic datasets in heart, lungs and musculoskeletal imaging has proven to be beneficial. [33][34][35][36][37] Spiral CT scanner can provide isotropic data.…”
Section: Introductionmentioning
confidence: 99%